2020
DOI: 10.1108/maj-08-2018-1969
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and compliance with IFRS 7

Abstract: Purpose This paper aims to investigate the impact of the characteristics of two corporate governance mechanisms, namely, board of directors and audit committee (hereafter AC), on the level of compliance with International Financial Reporting Standard [hereafter International Financial Reporting Standards (IFRS)] 7 “Financial instruments: Disclosures” (hereafter FID). Design/methodology/approach Using a self-constructed checklist of 128 items, this research measures the compliance with IFRS 7 of 63 Canadian f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…Abdullah (2011), Bagudo et al (2018), Almaqtari (2019), and Krismiaji (2019) found a positive relationship between the size of the audit committee and the degree of compliance with IFRS. Conversely, Affes and Makni-Fourati (2019), Juhmani (2017), Agyei-Mensah (2019b), and Mnif and Znazen (2020) did not find any significant relationship between this variable and compliance with IFRS. Based on these discussions, we hypothesize that:…”
Section: Hypothesis 3 (H3)mentioning
confidence: 73%
See 4 more Smart Citations
“…Abdullah (2011), Bagudo et al (2018), Almaqtari (2019), and Krismiaji (2019) found a positive relationship between the size of the audit committee and the degree of compliance with IFRS. Conversely, Affes and Makni-Fourati (2019), Juhmani (2017), Agyei-Mensah (2019b), and Mnif and Znazen (2020) did not find any significant relationship between this variable and compliance with IFRS. Based on these discussions, we hypothesize that:…”
Section: Hypothesis 3 (H3)mentioning
confidence: 73%
“…Although few studies have addressed this determinant, it has been shown to be a good determinant that helps to raise the level of disclosure and to increase compliance with IFRS (Ettredge et al 2011;Alkurdi et al 2019;Zango 2019). Conversely, several studies could not identify any significant association between the degree of compliance with IFRS and frequent audit committee meetings (Agyei-Mensah 2019a; Almaqtari 2019; Bagudo et al 2018;Ernawati and Aryani 2019;Mnif and Znazen 2020;Sellami and Fendri 2017). Based on these discussions, we hypothesize that:…”
Section: Audit Committee Meeting Frequencymentioning
confidence: 81%
See 3 more Smart Citations